Novel paradigm in AFM probe fabrication: Broadened range of stiffness, materials, and tip shapes. (February 2023) - Milczarek, Michał; Jarząbek, Dariusz M.; Jenczyk, Piotr; Bochenek, Kamil; Filipiak, Maciej
Abstract: Atomic force microscopes could be used in wide range of nanotribology experiments but probes available on the market are only made of silicon or silicon nitride with a stiffness in the range of 0.01–100 N/m, which significantly limits the possible research. We strive to solve this problem by designing all-metal probes. The proposed fabrication method is characterised by the use of a copper substrate and electrodeposition in a mould prepared by indentation and photolithography. Prototype probes fabricated with this method were made of nickel with a stiffness of 20 N/m and 2800 N/m and were used for topography and friction measurements. Both the method and all-metal probes showed flexibility and great potential, especially in the field of nano/microtribology.